Upholding Election Justice: The Election Supervisory Agency's Strategy to Monitor the Campaigns of Non-Candidate Regional Heads in Indonesia - Agatha, Insani Tiara; Jannah, Hidayatul (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
Issues related to whether or not regional heads who are not candidates can participate in campaigning in elections and regional elections have become a separate discourse in the Indonesian electoral law system due to contradictory rules. Therefore, the government seeks to realize electoral justice through strengthening the duties and functions of The Election Supervisory Agency as an institution authorized to oversee all stages of elections and regional elections. In this case, The Election Supervisory Agency or Bawaslu is responsible for ensuring that there are no violations committed by regional heads who are not candidates in the context of elections and regional elections, especially in the campaign stage which is very prone to violations. This research uses a type of library research with a normative juridical research method that uses conceptual approaches and laws and regulations. The result of this study is that The Election Supervisory Agency needs to reform the supervision mechanism in terms of legal substance, legal structure, and legal culture in order to achieve electoral justice in elections and regional elections.